Comparison of Two-Step Transient Evoked Otoacoustic Emissions and One-Step Automated Auditory Brainstem Response for Universal Newborn Hearing Screening Programs in Remote Areas of China - Sheng, Haibin; Zhou, Qian; Wang, Qixuan; Yu, Yun; Liu, Lihua; Liang, Meie; Zhou, Xueyan; Wu, Hao; Tang, Xiangrong; Huang, Zhiwu (Frontiers in Pediatrics, 2021)
Objective: To compare the hearing screening results of transient evoked otoacoustic emissions (TEOAE) and automatic auditory brainstem response (AABR) in non-risk newborns at different time after birth, and to explore a more suitable hearing screening mode for first screening within 48 hours after birth in remote areas of China. Methods: according to the first screening time, 2005 non-risk newborns were divided into three groups: p24h group, 673 cases, first screening time ≤ 24h; p48h group, 667 cases, first screening time was 24 ~ 48h; p72h group, 665 cases, first screening time was 48 ~ 72h. All subjects received TEOAE + AABR combined hearing screening, and those who failed in any test were rescreened with TEOAE + AABR at 6 weeks. The first screening results of AABR and TEOAE were compared among the three groups. The results of OAE two-step screening (first screening and re-screening were OAE) and AABR alone screening were compared for newborns who were screened within 48 hours. Results: the pass rate of AABR (93.8%) was significantly higher than that of TEOAE (91.2%). The passing rate of TEOAE and AABR increased significantly with the increase of first screening time (P < 0.05), and the false positive rate decreased significantly with the increase of first screening time (P < 0.05). The failure rate of first screening of AABR within 48 hours was 7.3%, which was significantly lower than that of TEOAE (9.9%) (P < 0.05). The average time spent on AABR was 12.51 ± 6.36min, which was significantly higher than that of TEOAE (4.05 ± 1.56min, P < 0.05). The failure rate of TEOAE two-step screening was 1.6%. Conclusions: Compared with TEOAE, AABR screening within 48 hours after birth can reduce the failure rate and false positive rate of first screening, but compared with OAE two-step screening, AABR alone screening has no obvious advantages in health economics. In our remote areas, one-step AABR screening is not feasible, OAE two-step screening program is still applicable to UNHS screening within 48 hours after birth.